ANALISIS MARJIN PEMASARAN AGROINDUSTRI BERAS DI KECAMATAN BUNGARAYA KABUPATEN SIAK - Ariaty, Widia; Rifai, Ahmad; Maharani, Evy (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Rice was important comodities for Indonesian society because almost 90 percent of Indonesian consume rice as their main food sources. Rice agroindustry was activitiy to produce rice to delivered to the consumer. A long process of supplying grain to be rice involves many marketing agencies.The purpose of this study was to analyze marketing channels and marketing margins in rice agroindustry. This study conducted during January 2015to September 2015. The location of this research was determined in four rice-producing centers in Bungaraya District. The number of sample in this research were 1 trader, 6 RMUs, 5 wholesalersÂ and 5 retailers through snowball sampling technique.The data collection was conducted with interview technique using questionnaire prepared previously.Data were analyzed by descriptive of the patterns of marketing channels and using analytical methods margin and costs in rice marketing. The results shows that there are three patterns of marketing channel in rice agroindustry, first: farmer-trader-RMU- wholesaler; secondly: farmer-RMU-wholesaler-retailer-consumer; third: farmer- RMU. The highest marketing margin were in RMU at 36,47 percent, then retailer 12,11 percent, and wholesaler 9,91 percent. Keyword: Rice, Agroindustry, Marketing Channels, Marketing Margin